Difunctional bionic self-resetting electromagnetic eddy current damping device - ZHAO HAILONG; ZHOU CHENHANG; LI XINGRONG; HUANG YONGHU; ZHANG HONGLI; XU PEIYUAN; TONG WENJUN; LUO WENJUN (2023)
The invention discloses a difunctional bionic self-resetting electromagnetic eddy current vibration damping device, which relates to the field of vibration damping and comprises a first fixed hinge support, two second fixed hinge supports, two bionic support members and a self-resetting electromagnetic eddy current core vibration damping unit, according to the bifunctional bionic self-resetting electromagnetic eddy current vibration reduction device, self-resetting of the whole structure is achieved through the self-resetting unit, meanwhile, through bionic supports similar to human leg structures, nonlinear adjustment of device control force along with the relative included angle and the change rate of the bionic supports is achieved, and the requirement for broadband vibration reduction is met; under the action of the energy collecting unit, the electric energy generated in the circuit is stored; a plurality of groups of eddy current units and magnetic supply units which can be adjusted are arranged in the